1996
DOI: 10.1097/00007890-199601270-00013
|View full text |Cite
|
Sign up to set email alerts
|

A Regional Experience With Emergency Liver Transplantation1

Abstract: Liver transplantation for patients requiring life-support results in the lowest survival and highest costs. A ten year (1983-1993) regional experience with liver transplantation for critically ill patients was undertaken to ascertain the fate of several subgroups of patients. Of the 828 liver transplants performed at six transplant centers within the region over this period, 168 (20%) were done in patients who met today's criteria for a United Network of Organ Sharing (UNOS) status 1 (emergency) liver transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…It can be argued whether it is worthwhile to proceed with retransplant or if retransplant should be avoided when the chance of survival is low,33–35 because it is well known that the sickest patients and retransplanted patients have the lowest survival rates and the highest hospital charges 36–37. PNF had incidences of complications as high as or higher than retransplants for other causes (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…It can be argued whether it is worthwhile to proceed with retransplant or if retransplant should be avoided when the chance of survival is low,33–35 because it is well known that the sickest patients and retransplanted patients have the lowest survival rates and the highest hospital charges 36–37. PNF had incidences of complications as high as or higher than retransplants for other causes (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Controversial aspects are the role of donor age and the length of the period of intensive care on the outcome of the patient. In this respect, studies have found no significant correlation with the recipient/graft outcome 29,30 although some authors have found an initial decay of function in grafts originating from aged donors 31,32 …”
Section: Discussionmentioning
confidence: 99%
“…These concerns were explored further to learn why those particular root causes had continued to occur (Step 7). The teams then developed risk-reduction strategies for our care process system-usually protocol changes-which our program instituted to improve our quality of care (Step 8; Table 7) [42][43][44][45][46][47].…”
Section: Resultsmentioning
confidence: 99%